The State amid the Threats of Cyber Democracy (Oratio Directa, 2020)
This article critically examines cyber democracy as a consequence of information and communication technology. A qualitative descriptive approach is used to analyze interaction, political participation, propaganda, conflict, and digital literacy in virtual public spaces. The discussion shows that cyber democracy broadens freedom of expression and political participation, but it also enables political actors to circulate hoaxes, hate speech, and identity-based propaganda. Misuse of anonymity and weak digital literacy produce a democratic deficit and may transfer polarization from virtual spaces into social life. Strengthening digital literacy, political awareness, and responsible communication is therefore essential to protect human rights and sustain democracy.
Keywords: Cyber democracy; Digital media; Propaganda; Social conflict; Digital literacy